A Sleep Intervention for Children with Autism Spectrum Disorder: A Pilot Study - Sarah A. Schoen; Sheryl Man (Scholarworks @ WMU, 2017)
Background: Parents of children who have Autism Spectrum Disorders (ASD) commonly report sleep problems, which typically exacerbate daytime behavior problems. This pilot study sought to identify the short-term effects on sleep, behavior challenges, attention, and quality of life of children with ASD following use of the iLs Dreampad ™ pillow, which delivers bone conducted music and environmental sounds. Aims were to demonstrate acceptability and feasibility, identify measures sensitive to change, and describe individual characteristics responsive to change. Method: Parent report questionnaires assessed sleep behavior, attention, autism-related behaviors, and quality of life from 15 participants before and during intervention. A Sleep Diary documented average sleep duration and average time to fall asleep during the preintervention phase and the last 2 weeks of the treatment phase. Results: Procedures were acceptable and feasible for families. All measures were sensitive to change. Children with ASD demonstrated significant change in sleep duration and time needed to fall asleep from pretest to intervention. Improvements were noted in autism-related behaviors, attention, and quality of life. Parent satisfaction was high. Conclusions: The iLs Dreampad™ pillow may be one alternative intervention to pharmacological interventions for children with ASD who have sleep problems. Further study is warranted.